Improvement of deep drawability of ultra-fine grained 6000 series aluminum alloy by tailored heat treatment - Herrmann, Jürgen; Merklein, Marion (Procedia Manufacturing, 2018)
Among other approaches like alloying, it is possible to increase the strength of aluminum sheet material by the application of processing techniques like Accumulative Roll Bonding. However, the ductility will be reduced, which results in a limited formability in deep drawing operations. In this context, the Tailor Heat Treated Blanks technology is a well-known approach to enhance the forming limits of conventional precipitation hardenable aluminum alloys. The local softening of a blank can be achieved by a short-term heat treatment, which causes a dissolution of the MgSi-clusters in the heat treated zones. In a subsequent deep drawing operation, the material flow can be improved from the softened towards crack-critical areas. Within this investigation, the method of Tailor Heat Treated Blanks is transferred to a multi-layered, ultra-fine grained sheet material of the aluminum alloy AA6014 in order to investigate the effect of a local short-term heat treatment on the forming limits in deep drawing. In a first step, a material characterization in dependency of different heat treatment temperatures is carried out. The strength and ductility, as well as the bond strength of the multi-layered sheets, are investigated. Concluding, the effect on the formability is examined by deep drawing experiments on cylindrical cups in combination with a local heat treatment of the outer flange area prior to the forming step. The results regarding the limiting drawing ratio are compared with a conventional sheet material in the T4 temper condition and a multi-layered sheet material without heat treatment. The investigations indicate that the drawability can be enhanced significantly by the combination of both methods.
LFT Import::2019-07-29 (2318)
Keywords: Accumulative roll bonding; Aluminum alloy; Deep drawing; Laser; Sheet metal; Tailor heat treated blanks